Short Course on Industrialized Building System (IBS) - Anon (Universiti Malaysia Perlis (UniMAP), 2011)
Short Course on Industrialized Building System (IBS), 25th July 2011 was organized by School of Environmental Engineering, Universiti Malaysia Perlis (UniMAP) and KUKUM Engineering (Malaysia) Sdn. Bhd. in collaboration with Proven IBS Training Centre (M) Sdn. Bhd.